2008
DOI: 10.1080/02786820801992907
|View full text |Cite
|
Sign up to set email alerts
|

A Source Dilution Sampling System for Characterization of Engine Emissions under Transient or Steady-State Operation

Abstract: With increasingly stringent regulations being placed upon engine emissions, an in-depth understanding of engine exhaust composition will be necessary to assess environmental and health impacts and to develop better methods of reducing emission levels. Source sampling systems have commonly utilized partial sampling techniques, which may introduce the potential for particle loss, and steady-state operation, which is incapable of imitating transient engine conditions. In order to simulate atmospheric dilution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Numerous other source testing investigations have employed similar techniques to collect fresh emissions, so each sample configuration will only be briefly discussed. Diesel samples were collected from a constant volume sampler (CVS) emission tunnel (Cummins Emission Solutions, Stoughton, WI) in which a subsample stream of primary diluted exhaust was introduced to a residence time chamber and completely mixed with filtered and dried secondary dilution air [ Liu et al ., ; Robinson et al ., ]. The secondary diluted sample was passed through a Dekati thermodenuder (TD, Dekati, Kangasala, Finland) at one of two temperature set points, 30°C as the nondenuded conditions and 300°C as a denuded condition.…”
Section: Methodsmentioning
confidence: 98%
“…Numerous other source testing investigations have employed similar techniques to collect fresh emissions, so each sample configuration will only be briefly discussed. Diesel samples were collected from a constant volume sampler (CVS) emission tunnel (Cummins Emission Solutions, Stoughton, WI) in which a subsample stream of primary diluted exhaust was introduced to a residence time chamber and completely mixed with filtered and dried secondary dilution air [ Liu et al ., ; Robinson et al ., ]. The secondary diluted sample was passed through a Dekati thermodenuder (TD, Dekati, Kangasala, Finland) at one of two temperature set points, 30°C as the nondenuded conditions and 300°C as a denuded condition.…”
Section: Methodsmentioning
confidence: 98%
“…Samples for both the ultra-low emissions gravimetric method and chemical reconstruction method were collected using a source dilution sampling system consisting of a primary dilution tunnel, a secondary-micro diluter, a residence time chamber (RTC), and multiple sampling trains (Liu et al 2008b). The exhaust gas from the engine was piped into a critical flow venturi-constant volume system (CFV-CVS) tunnel where it was mixed with pre-, activated carbon-, and HEPA-filtered air at a rate of 1.298 m 3 /s.…”
Section: Test Equipment and Proceduresmentioning
confidence: 99%
“…Other studies have also shown that implementation of aftertreatment systems, such as DPFs, alters emissions compositions (Lev-on et al 2002;Liu et al 2008a). In comparison to the high-PM emissions of older engines, the ultra-low PM emissions of modern engines have been shown to exhibit a less stable composition (Birch and Cary 1996;Kleeman et al 2000;Liu et al 2008b). The solid fraction of PM in ultra-low emissions is largely filtered by the DPF, leaving an increased organic fraction and yielding a relative enrichment in semi-volatile organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Before conducting test experiments, the sampling dilution system components were disassembled, cleaned, air dried, assembled, and 'tested for leaks to prevent contamination from the surrounding air' 37 to avoid contamination of the emissions with organic and metal compounds from previous burn sequences. High power compressed air and water were used to remove large particles from the sampling channels.…”
Section: Quality Controlmentioning
confidence: 99%